2007
DOI: 10.1096/fj.06-7537com
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐related weak inducer of apoptosis (TWEAK) is a potent skeletal muscle‐wasting cytokine

Abstract: TWEAK cytokine has been implicated in several biological responses including inflammation, angiogenesis, and osteoclastogenesis. We have investigated the role of TWEAK in regulating skeletal muscle mass. Addition of soluble TWEAK protein to cultured myotubes reduced the mean myotube diameter and enhanced the degradation of specific muscle proteins such as CK and MyHCf. The effect of TWEAK on degradation of MyHCf was stronger than its structural homologue, TNF-alpha. TWEAK increased the ubiquitination of MyHCf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
293
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 219 publications
(306 citation statements)
references
References 76 publications
(117 reference statements)
9
293
0
4
Order By: Relevance
“…Nevertheless, it appears that the TWEAK-Fn14 system is active in processes related to growth and remodeling of tissue and organs during development and tissue repair. In accordance with this, animal studies implicated the TWEAK-Fn14 system in liver progenitor cell proliferation (6,7), regulation of muscle development and muscle regeneration (8)(9)(10)(11), tumor-associated angiogenesis (12), and in various inflammationrelated pathologies including graft-versus-host disease, systemic lupus erythematosus-related nephritis (13), 2,4,6-trinitrobenzene sulfonic acid-induced colitis (14), renal and cerebral ischemia (15)(16)(17)(18), and collagen-induced arthritis (19,20).…”
mentioning
confidence: 66%
“…Nevertheless, it appears that the TWEAK-Fn14 system is active in processes related to growth and remodeling of tissue and organs during development and tissue repair. In accordance with this, animal studies implicated the TWEAK-Fn14 system in liver progenitor cell proliferation (6,7), regulation of muscle development and muscle regeneration (8)(9)(10)(11), tumor-associated angiogenesis (12), and in various inflammationrelated pathologies including graft-versus-host disease, systemic lupus erythematosus-related nephritis (13), 2,4,6-trinitrobenzene sulfonic acid-induced colitis (14), renal and cerebral ischemia (15)(16)(17)(18), and collagen-induced arthritis (19,20).…”
mentioning
confidence: 66%
“…It is also notable that Fn14 is expressed at high levels in developing skeletal muscle of neonatal/young mice. However, Fn14 levels are dramatically reduced in skeletal muscle of adult mice (9). Although it is possible that growth factors play a role in the expression of Fn14 in skeletal muscle during development, they are not the key regulators of Fn14 expression in denervated muscle of adult mice because the expression of some of these factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Adult skeletal muscle expresses minimal levels of Fn14 in unchallenged conditions (8,9). Although the expression of TWEAK does not change significantly, loss of nerve supply causes a rapid and robust increase in the expression of Fn14 in skeletal muscle (8).…”
mentioning
confidence: 99%
“…We have recently reported that tumor necrosis factor (TNF)-related weak inducer of apoptosis (TWEAK), a proinflammatory cytokine belonging to the TNF superfamily, is a potent skeletal muscle-wasting cytokine (13). Although the exact mechanisms of action of TWEAK in skeletal muscle remain unknown, TWEAK has been found to inhibit the differentiation of myoblasts into myotubes (14).…”
mentioning
confidence: 99%
“…Although the exact mechanisms of action of TWEAK in skeletal muscle remain unknown, TWEAK has been found to inhibit the differentiation of myoblasts into myotubes (14). TWEAK also augments the degradation of specific muscle proteins such as MyoD and myosin heavy chain fast type in cultured muscle cells (13,15). Furthermore TWEAK-induced muscle atrophy in vivo is accompanied with significant extracellular matrix abnormalities (13).…”
mentioning
confidence: 99%